Laicidade, liberdade religiosas e suas construções no Estado brasileiro - Vital, Pablo Henrick Oliveira Leite (2024)
This study aims to deepen the historical construction of religious freedom and secularism. Secularism and religious freedom have undergone several modifications throughout Brazilian constitutional history. The religiosity brought by Europeans and Africans, added to the beliefs of indigenous peoples, formed the cultural bases of the Brazilian people, as well as influencing the formation of the State. Secularism and religious freedom in Brazil underwent a historical construction, beginning in the colonial period, marked by a strong connection between the Roman Catholic Apostolic Church, going through small concessions so that other religious manifestations were accepted by the State. Only after Decreto 119-A of 1890, there was a separation between Church and State, allowing the Brazilian State to be effectively secular. The objective of this study is an in-depth analysis of the influence of religious freedom and secularism in the construction of the Brazilian State, going through Brazilian constitutional history, observing how these two institutes were treated in the Letters, even in confessional ones such as that of 1824. It is expected that This research contributes to a better understanding of the constitutional history of Brazil, as well as the observation of religious influence in the construction of a State